Utilization of Jengkol Peel (Pithecellobium jiringa) as an Adsorbent of Iron Metal - Mutiara Fildza; Rohmatullaili Rohmatullaili; Ade Oktasari (Department of Chemistry Faculty of Science and Technology Walisongo, 2022)
Cellulose, which has the active group OH, is found in Jengkol peel. Jengkol peel has the potential to be utilized as an adsorbent for Iron (Fe) metal because it contains these active groups. The FT-IR spectrophotometer instrument was used to confirm the presence of the -OH group in the Jengkol peel adsorbent, which was observed at the peak of the OH vibration at wave number 3293 cm1. Utilizing NaOH (0.1 M), the active group was activated. With an adsorption percentage of 96.24%, pH 7 was the optimum adsorption pH. With an adsorption percentage of 99.20%, 25 minutes was indeed the optimum contact time. With an adsorption capacity value of 8.581 mg/g, the binding of Fe metal by the adsorbent active group occurs in the complex formation mechanism, it was indicating a relatively high adsorption efficiency.